Radon Sources and Associated Risk in Terms of Exposure and Dose - Vogiannis, Efstratios G.; Nikolopoulos, Dimitrios (Frontiers in Public Health, 2015)
Radon concern the international scientific community from early 20th century. Initially as radium emanation, almost the second half of the century as severe harmful to human health. Initial brilliant period of use as medicine, followed by a period of intense concern for its health effects. Primary target groups surveyed were miners early in Europe later in U.S. There is now compelling evidence that radon and its progeny can cause lung cancer. Human activities may create or modify pathways increasing indoor radon concentration compared to outdoor background. These pathways can be controlled by preventive and corrective actions. Indoor Radon and its short-lived progeny attached on aerosol particles or free compose an air mixture that carry a significant energy amount (PAEC). Exposure on PAEC and dose delivered reviewed in detail. Special attention was paid to the case of water workers because lack of adequate data. Radon risk assessment and current legislation regulates dose from radon and its progeny, also were reviewed.